WORLD TRADE ORGANIZATION: ON THE FACILITATION OF CUSTOMS PROCEDURES FOR TRADE. PART II - Natalia A. Vorontsova (Московский журнал международного права, 2018)
INTRODUCTION. Considering close attention of the states to the work of the World Trade Organization, the interest is undoubtedly attracted by new agreements, adopted by it and based on current trends of trade development and aspiration of the states to conduct foreign economic activity more productively and without barriers. In particular, the article concerns Agreement on Trade Facilitation, adopted in 2014. The article tackles peculiarities of providing privileges for developing and least developed countries with respect to application of Agreements’ provisions, as well as tariff preferences concerning goods originating in these countries on the example of the EEU.MATERIALS AND METHODS. During the research the author has used international conventions, adopted within both the World Trade Organization, and World Customs Organization, modern doctrinal research of Russian and foreign authors. The methodological basis of the research constitute method of the systematical and logical analysis, dialectic method, legal-historical, comparative law and technical juridical methods.RESEARCH RESULTS. In the course of the conducted research the author notes that the Agreement’s provisions relating to the special and differential treatment for developing and least developed countries are very progressive. An innovation is the possibility of application of obligations under the Agreement by least developed countries only in part, which corresponds to their individual level of development, financial and trade needs. Unlike Section I of the Agreement, concerning which the author drew very skeptical conclusions in the previous article, Section II is rather innovative and provides actual mechanisms of support for the least developed countries.DISCUSSION AND CONCLUSIONS. The author analyzes provisions of the Trade Facilitation Agreement (further – the Agreement) that was adopted in 2013 and came into force in 2017, which is directly included in the Appendix 1A of the WTO Agreement, after the Agreement on Safeguards. The article tackles provisions, relating to the special and differential treatment for developing and least developed countries. Besides, the author analyzes theoretical aspects of categorizing states as such. The author gives examples of providing tariff preferences for goods originating in developing and least developed countries, of conditions and application standard of the EEU uniform system of tariff preferences, the list of such countries. Comparing and analyzing international agreements on these matters, the author comes to the following conclusions. Provisions of Section II of the Agreement differ from earlier established ones concerning developing and least developed countries, provide more preferential terms of application of the Agreement, taking into account potentialities of the country. At the same time, very important is the principle of individual approach to each such country, which independently defines a possibility of application of the Agreement provisions. Besides, an opportunity to simultaneously demand help for capacity-building is, of course, quite progressive for such agreements. The author notes that the EEU provisions concerning goods, originating in developing and the developed countries – users of the Union uniform system of tariff preferences, meet international standards and promote economic progress of developing and least developed countries.